Estudo do algoritmo ADAMF na detecção de afundamento de tensão - Sousa, Jeymyson Alves de (2017)
Voltage sag has become a remarkable concern in the field of power quality, mainly due to the growth of sensitive loads connected to our power grid. Research conducted by Electric Power Research Institute-EPRI shown that more than 40 % of energy quality events are related to voltage sag, and the amount of finacial loss caused by those events are considered.The financial loss in american industrial sector reachs every year $ 114 bilions. For this reason, this work aims to make a study of the ADAMF algorithm for detection of voltage sags, and propose an adjustment to characterize the type of sag. The ADAMF algorithm, studied in this work, uses the aggregate value of the voltage in the reference frame ab, in order to detect the sags. This algorithm are able to detect symmetric and assymetric voltage sags, due its ability to independently monitor the fundamental voltage componet of each phase. Six simulation scenarios were carried out in order to validate the efficiency of this algorithm.The results were satisfactory, as the algorithm was able to detect the sag, as well as characterize its type. Also, the DSOGI (Double Second Order Generalized Integrator) filter shown efficiency as the aggregate value of fundamental voltage component in the presence of harmonics were similar to the aggregate value of fundamental voltage component without harmonics.